2003
DOI: 10.1590/s1415-47572003000400014
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome characterization in Thinopyrum ponticum (Triticeae, Poaceae) using in situ hybridization with different DNA sequences

Abstract: Thinopyrum ponticum (2n = 10x = 70, JJJJ s J s ) belongs to the Triticeae tribe, and is currently used as a source of pathogen resistance genes in wheat breeding. In order to characterize its chromosomes, the number and position of 45S and 5S rDNA sites, as well as the distribution of the repetitive DNA sequences pAs1 and pSc119.2, were identified by fluorescent in situ hybridization. The number of nucleoli and NORs was also recorded after silver nitrate staining. Seventeen 45S and twenty 5S rDNA sites were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Considering that, during mitosis, active NORs possess transcription factors of rDNA genes, that impregnate with silver (Morais-Cecílio et al 2000, Besendorfer et al 2002, Brasileiro-Vidal et al 2003, Neves et al 2005, the presence of a single active NOR was confirmed at the portion of chromosome 1 adjacent to the centromere, in B. arborea (Fig. 1c), indicating that this region contains the chromosomal domain around which nucleoli are organized at the end of mitosis, when rDNA transcription is initiated.…”
Section: Discussionmentioning
confidence: 88%
“…Considering that, during mitosis, active NORs possess transcription factors of rDNA genes, that impregnate with silver (Morais-Cecílio et al 2000, Besendorfer et al 2002, Brasileiro-Vidal et al 2003, Neves et al 2005, the presence of a single active NOR was confirmed at the portion of chromosome 1 adjacent to the centromere, in B. arborea (Fig. 1c), indicating that this region contains the chromosomal domain around which nucleoli are organized at the end of mitosis, when rDNA transcription is initiated.…”
Section: Discussionmentioning
confidence: 88%
“…Secondary constrictions can be observed by conventional chromosome staining techniques, but are more easily identified by silver nitrate (Ag) staining or in situ hybridization with 45S rDNA probes (see e.g. Brasileiro-Vidal et al, 2003). These constrictions are largely known as 45S rDNA location sites, although smaller or less active 45S rDNA sites may exist in chromosomes which apparently do not form secondary constrictions (Guerra et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…During mitosis, the active NORs are those where rDNAs are associated with proteins that associate themselves with silver (Roussel , 1996;Morais-Cecílio et al, 2000;Besendorfer et al, 2002;Brasileiro-Vidal et al, 2003;Almeida & Carvalho, 2004;Neves et al, 2005;Clarindo & Carvalho, 2006). The presence of the active NOR on pairs (1 and 2) indicates, according to Mergonar et al (2010), that these chromosomal regions have chromosome domains around which nucleoli at the end of mitosis are arranged, when the rDNA transcription is initiated.…”
Section: Resultsmentioning
confidence: 99%